Design and Implementation of a Lightweight Security-Enhanced Scheme for Modbus TCP Protocol. (13th April 2023) - Liu, Zechao; Liang, Tao; Wang, Wenshan; Sun, Ruochen; Li, Sizhao
Abstract : The advent of Industry 4.0 has made people pay more and more attention to the security of the industrial control system. As a common and typical communication protocol, Modbus does not consider the problem of data security at the beginning of its design, which provides opportunities for criminals. In this paper, we design a security scheme to protect the traditional Modbus TCP protocol, by using domestic encryption algorithms. As a result, the proposed scheme is able to identity authentication, data encryption, data integrity check, and anti-replay attacks. Security analysis and experimental results show that our proposed scheme solves the security problem of Modbus TCP protocol with minimal overhead increase.